Peningkatan UI/UX Learning Management System Melalui Redesain Berbasis Design Thinking - Harfin Aqbil Falah; Fajri Rakhmat Umbara; Herdi Ashaury (Jurnal Algoritma, 2026)
The Learning Management System (LMS) at SMKN 4 Padalarang faces various problems in terms of interface and user experience due to the use of default Moodle templates that are not designed according to user needs. An unintuitive interface, confusing navigation, and unattractive visual aesthetics are obstacles to the effectiveness of online learning. This study aims to evaluate the effectiveness of the Design Thinking method in improving the quality of the LMS UI/UX through a user-centered approach. The testing methods used include the System Usability Scale (SUS), User Experience Questionnaire (UEQ), and A/B Testing. Before the redesign, the average SUS score was only 45, which falls into the “Awful” (F) category, and the UEQ results showed an average value below -0.8, which is a negative evaluation. After implementing the Design Thinking method, the SUS score increased to 85, which falls into the “Excellent” (A) category, and the A/B Testing results showed that users preferred the new design, especially in terms of navigation, visuals, and ease of use. These findings indicate that the Design Thinking approach is not only effective in improving usability and functionality, but also capable of increasing user satisfaction and comfort in using the LMS.